CONTRACT DESIGN WITH LIMITED COMMITMENT - Vitali Gretschko; Achim Wambach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We consider the problem of a principal who wishes to contract with a privately informed agent and is not able to commit to not renegotiating any outcome of any mechanism. We provide a general characterization of renegotiation-proof outcomes. We apply the solution to a setting with a continuous type space, private values and non-linear contracts. We find that the optimal renegotiation-proof outcomes for the principal are pooling outcomes and satisfy a “no-distortion-at-the-bottom” property.
Keywords: C72; 330